Analisis Pengaruh Rasio Profitabilitas dan Rasio Likuiditas terhadap Nilai Perusahaan Subsektor Otomotif yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2024 - Anjelita, Aprilia; Maithy, Sifera Patricia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the effect of liquidity ratios and profitability ratios on the value of automotive subsector companies listed on the Indonesia Stock Exchange (IDX) during 2021-2024. The subjects of this study are eight automotive companies selected based on the availability of financial reports. Firm value is measured using Price Book Value (PBV), while profitability ratios are measured using Return On Assets (ROA) and liquidity ratios are measured using Current Ratio (CR). The research method used was quantitative, with data processing conducted using SPSS software. The results of the regression analysis indicate that ROA has a positive and significant influence on PBV, with a coefficient value of 12.340 and significance of 0.000. Conversely, CR does not show a significant effect on PBV, with a coefficient value of -0.027 and significance of 0.653. The coefficient of determination shows that 84.8% of the variation in PBV can be explained by the independent variables studied, while the remaining 15.2% is influenced by other factors not studied in this research. From the results of this study, it can be concluded that profitability ratios, particularly ROA, are more dominant indicators in influencing company value than liquidity ratios. These findings are expected to provide insights for investors and automotive company management in decision-making related to increasing company value. This study also suggests the need to pay more attention to other factors that may influence company value in the future.